Editorial - George R. Saade (Thieme Medical Publishers, Inc., 2011)
As this is the first issue of 2011, I would like to take this opportunity to update our readers on few improvements in the journal, highlight some of the obstetric articles we published in the past year, and address a mea culpa to the authors who submitted manuscripts to the journal in the past 6 months.